Fatty acid photodecarboxylase is an ancient photoenzyme that forms hydrocarbons in the thylakoids of algae. Issue 3 (15th April 2021) - Moulin, Solène L Y; Beyly-Adriano, Audrey; Cuiné, Stéphan; Blangy, Stéphanie; Légeret, Bertrand; Floriani, Magali; Burlacot, Adrien; Sorigué, Damien; Samire, Poutoum-Palakiyem; Li-Beisson, Yonghua; Peltier, Gilles; Beisson, Fred
Abstract : Most algal lineages have the ability to produce hydrocarbons in thylakoids of the chloroplast. Abstract: Fatty acid photodecarboxylase (FAP) is one of the few enzymes that require light for their catalytic cycle (photoenzymes). FAP was first identified in the microalga Chlorella variabilis NC64A, and belongs to an algae-specific subgroup of the glucose–methanol–choline oxidoreductase family. While the FAP from C. variabilis and its Chlamydomonas reinhardtii homolog CrFAP have demonstrated in vitro activities, their activities and physiological functions have not been studied in vivo. Furthermore, the conservation of FAP activity beyond green microalgae remains hypothetical. Here, using a C. reinhardtii FAP knockout line ( fap ), we showed that Cr FAP is responsible for the formation of 7-heptadecene, the only hydrocarbon of this alga. We further showed that Cr FAP was predominantly membrane-associated and that >90% of 7-heptadecene was recovered in the thylakoid fraction. In the fap mutant, photosynthetic activity was not affected under standard growth conditions, but was reduced after cold acclimation when light intensity varied. A phylogenetic analysis that included sequences from Tara Ocean identified almost 200 putative FAPs and indicated that FAP was acquired early after primary endosymbiosis. Within Bikonta, FAP was retained in secondary photosynthetic endosymbiosis lineages but absent from those that lost the plastid. Characterization of recombinant FAPs from various algal genera ( Nannochloropsis, Ectocarpus, Galdieria, Chondrus ) provided experimental evidence that FAP photochemical activity was present in red and brown algae, and was not limited to unicellular species. These results thus indicate that FAP was conserved during the evolution of most algal lineages where photosynthesis was retained, and suggest that its function is linked to photosynthetic membranes.